Phenomenology of Divorce Through Social Media in Muslim Societies - Sobri, Sobri; Wira, Ahmad; Subagio, Mukhamad Hadi Musolid (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Divorce in Muslim society has become a complex and concerning phenomenon. Advances in technology and the widespread use of social media have influenced the dynamics of divorce in this society. This study aims to understand the phenomenology of divorce through social media in Muslim society using a qualitative phenomenological approach. The results of the study indicate that social media plays an important role in the divorce process, both as a cause and as a consequence. Factors such as lack of communication, suspicion, and the influence of social media on household relationships are the main causes of divorce. In addition, social media is also used as a means to announce divorce, seek emotional support, and build post-divorce identity. Therefore, there is a need for awareness of the impact of social media on household relationships, the importance of effective communication and trust in the household and the need for support from family, society and religious institutions. Therefore, Muslim society must increase public awareness about the impact of social media, develop household education and counseling programs, and strengthen the role of religious institutions in supporting families.